The Influence of Earnings Manipulation, Strength of Financial Position, Financial Distress and Capital Structure on Firm Value - Destiya Nurmala Putri; Dina Novriyana (Journal of Accounting and Auditing, 2026)
Purpose – This study focuses on the influence of earnings manipulation, financial position strength, financial distress, and capital structure on firm value. Design/methodology/approach – This study uses a quantitative method. By using secondary data. With a population of 166 companies in the non-primary consumer goods sectors listed on the Indonesia Stock Exchange in 2022 and 2024. The sample for this study consists of 45 companies listed on the Indonesia Stock Exchange in 2022 and 2024. The total number of observations is 135. The total number of observations in this study is 135. The analysis technique used to test the hypotheses is multiple regression analysis using Eviews9 software Findings – The results of this study indicate that earnings management variables have a negative and insignificant effect on firm value. Financial position strength variables have a negative and insignificant effect on firm value. Financial distress variables have a positive and significant effect on firm value. Capital structure variables have a positive and significant effect on firm value. Research limitations/implications – This study aims to provide information about company value and can be beneficial for decision-making as well as serve as a reference for further research. JEL : G30, G32, G33, M41